KONTRIBUSI LEMBAGA KEUANGAN MIKRO SYARIAH TERHADAP PEMBERDAYAAN PEREMPUAN (STUDI KASUS BMT DI KABUPATEN SLEMAN YOGYAKARTA) - Ninik Sri Rahayu; Rr. Sita D. Kusumaningrum (UII, 2015)
This study aims at exploring the contribution of Sharia Microfinance Institution (Baitul Maal wat Tamwil-BMT) on women empowerment using quantitative as well as qualitative method of analysis. There are five BMTs in Kabupaten Sleman that have been operating more than five years used as the population of study. In more detail, this study takes microentrepreneurs women who have been joining BMT minimal for two years as the samples of study by using Multistage Area Sampling Methods. The dependent variables consist of control over saving and income, ownership, decision-making, self-efficacy, self-esteem, mobility, and participation of activities outside home.The statistical analysis using Mann Whiteney U Test results in two research findings, namely 1) This study shows a significant difference on control over savings and income, decision-making, mobility, and participation of activities outside home between women members of BMTs and non-members. 2) This study shows no significant difference on self-efficacy and self-esteem between women members of BMTs and non-members.Based on research findings, this study recommends several points, namely 1) it is necessary for the next research to increase the minimal number of respondent so that they can represent the real situation. 2) The biggest segments of BMTs are merchants/traders as well as microentrepreneurs women. Therefore, it is important for BMTs to develop more women empowerment oriented programs. 3) The next research should explore the impact of BMTs on gender relation in the family and its implication for women. This is important since in the culture of Indonesian society, especially in Yogyakarta, the practices of patriarchy are still firmly rooted Keywords: Empowerment, Women, BMT